Understanding the Need for Situational Handling During Natural Hazards: An Attitudinal Study Among School Students - Dr. Sidra Kiran; Shafqat Ibrahim; Sameena Arif; Wajid Mahnaz (Indus Journal of Social Sciences, 2025)
The increasing incidence of natural disasters necessitates a structured approach to disaster preparedness and response. The World Disaster Report states that over 200 million people are affected by natural disasters annually, with children being among the most vulnerable groups. Schools play a crucial role in disaster risk reduction (DRR), as they provide a structured environment where students can learn critical survival skills. The study aimed at “Understanding the Need for Situational Handling During Natural Hazards: An Attitudinal Study Among School Students”. The objectives of the study were, 1) To measure the attitude of students towards the need of disaster management training during earthquake at school level. 2) To investigate the current status of disaster management training during earthquake at school level.. The population for this research comprised employees working in higher secondary schools in the Rawalpindi/Islamabad area who are involved in disaster management, including both trained and untrained personnel, for the academic year 2023–2025. In the study, the sample size was expanded to increase the robustness and generalizability of the findings. The total population remained the same, comprising 1,480 students and 300 teachers. The sample included 148 students and 30 teachers, with a total sample size of 178 participants. Similar to the pilot study, the final study also achieved a 100% response rate. The findings suggest that while 90% of respondents feel confident that disaster management training prepares them for earthquakes, concerns remain regarding emergency supplies, with 90% believing classrooms lack essential resources. Additionally, 73% trust that structural safety checks are conducted, but 60% feel evacuation plans are not well-practiced, highlighting gaps in preparedness. Hence, it is recommended that schools should conduct a thorough assessment of emergency supply stockpiles and ensure that all classrooms and common areas are well-equipped. Regular evacuation drills should be conducted in collaboration with emergency response teams to improve students’ familiarity with evacuation procedures. Moreover, periodic structural safety inspections should be reinforced with transparent reporting to build trust in school infrastructure integrity.